Design characteristics of the horizontal steam generator PGV-1000 - Yefimov, Olexander Vyacheslavovich; Tiutiunyk, Larysa Ivanivna; Harkusha, Tetyana Anatoliivna; Yesypenko, Tetyana Oleksiivna; Motovilnik, Anastasiia Vadimovna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The materials of the article consider the design characteristics of horizontal steam generators PGV-1000 for WWER NPPs. The NPP steam generator, in particular the PGV-1000 steam generator, is a specific heat exchange unit. This unit, together with a nuclear reactor and a steam turbine, is one of the main equipment of multi-circuit (double-circuit) steam turbine NPPs. The steam generator produces working steam using heat dissipated from the reactor core by the cooling medium and sent to the heat exchange surface of the steam generator. NPP steam generators, connecting the contours of the coolant and the working substance, equally belong to each of them. The heat-absorbing medium in the steam generator is the working substance (water, steam). PGV-1000 type NPP steam generators with pressurized water reactors produce dry saturated steam. The requirement to maintain high purity of the coolant is due to the heat transfer surfaces of such steam generators made of austenitic stainless steel with electropolished surfaces. WWER reactors do not allow the coolant to boil in the core, so the temperature of the coolant at the outlet of the reactor (at the inlet to the steam generator) is always lower than the saturation temperature corresponding to the water pressure in the coolant circuit. Underheating of the coolant to the saturation temperature (approximately 25 ÷ 30 °С) guarantees the exclusion of vaporization even in the most loaded reactor channels. The design characteristics of modern horizontal steam generators such as PGV-1000 of various modifications provide high technical and economic performance of NPP units with WWER-1000 and high maintainability, which allows to extend the service life of domestic NPPs.

У матеріалах статті розглянуто конструктивні характеристики горизонтальних парогенераторів ПГВ-1000 для АЕС ВВЕР. Парогенератор АЕС, зокрема парогенератор ПГВ-1000, є специфічною теплообмінною установкою. Цей агрегат разом з ядерним реактором і паровою турбіною є одним з основних устаткування багатоконтурних (двоконтурних) паротурбінних АЕС. Парогенератор виробляє робочу пару, використовуючи тепло, що розсіюється від активної зони реактора охолоджуючим середовищем і направляється на теплообмінну поверхню парогенератора. Парогенератори АЕС, з'єднуючи контури теплоносія і робочої речовини, однаково належать кожному з них. Теплопоглинаючим середовищем у парогенераторі є робоча речовина (вода, пара). Парогенератори АЕС типу ПГВ-1000 з водоводяними реакторами виробляють суху насичену пару. Вимога дотримання високої чистоти теплоносія обумовлена теплообмінними поверхнями таких парогенераторів з аустенітної нержавіючої сталі з електрополірованими поверхнями. Реактори ВВЕР не допускають кипіння теплоносія в активній зоні, тому температура теплоносія на виході з реактора (на вході в парогенератор) завжди нижче температури насичення, що відповідає тиску води в контурі теплоносія. Недогрів теплоносія до температури насичення (приблизно 25 ÷ 30 °С) гарантує виключення пароутворення навіть у найбільш завантажених каналах реактора. Конструктивні характеристики сучасних горизонтальних парогенераторів типу ПГВ-1000 різних модифікацій забезпечують високі техніко-економічні показники блоків АЕС з ВВЕР-1000 та високу ремонтопридатність, що дозволяє продовжити термін служби вітчизняних АЕС.
Конструктивні характеристики горизонтального парогенератора ПГВ-1000
Keywords: horizontal steam generator PGV-1000; mathematical model; design characteristics; горизонтальний парогенератор ПГВ-1000; математична модель; конструктивні характеристики